Bioethanol production from rice husk of Dahanala red naadu using Saccharomyces cerevisiae and yield enhancement by optimization of growing conditions - Christy, E.J.S.B.A.; Branavan, K. (University of Jaffna, 2024)
The world currently relies predominantly on non-renewable fossil fuels, leading to a severe energy crisis marked by escalating oil prices and detrimental effects of fossil fuel combustion. Over-consumption of these fuels is causing widespread air pollution through greenhouse gas emissions, contributing to hazardous environmental crises such as the greenhouse effect, global warming, and acid rain. This urgent situation underscores the need for a swift transition to sustainable energy sources. Since the paddy plant parts other than grain are underutilized in most of the countries, the usage of paddy husk as a substrate for the bioethanol production was tried. Thus, the objective of the research was to identify the most efficient variety of paddy husk source for bioethanol production in Sri Lanka and to optimize the fermentation conditions in order to improve the ethanol yield. When the husk of different paddy varieties such as Pachapperumal, Sammba, Rath suwandel, Dahanala Red naadu, Dik wee, Kuruluthuda and Naadu rice were used as substrate for the action of Saccharomyces cerevisiae, significantly higher amount of bioethanol was produced with Dahanala type of longgrain red rice variety, thus it was selected for further studies. When the substrate concentration of the medium was optimized as 90%, the ethanol yield showed a significant increase by 2.6 times than the control 25%. When the media pH was optimized as 6.0, bioethanol output was increased significantly by 1.2 times than the control pH (7.0). When the incubation period was optimized as 30 hours, significantly higher ethanol yield was obtained. Ethanol production was significantly higher at 25oC than the control (room temperature). After the optimization, the bio ethanol yield showed a significant increase by 9.4 times in Dahanala type paddy husk than that of the conditions non-optimized. A comprehensive fermentation study, conducted on a large-scale using bioreactors, is imperative to assess the commercial viability of the identified findings.
Keywords: Bioethanol; Dahanala red naadu; Fermentation; Paddy husk; Saccharomyces cerevisiae